Thrombotic complications of myeloproliferative neoplasms: risk assessment and risk‐guided management. Issue 7 (15th July 2013) - Casini, A.; Fontana, P.; Lecompte, T.P.
Summary: Philadelphia‐negative myeloproliferative neoplasms are considered to be acquired thrombophilic states. Thromboses, both arterial and venous (not rarely in unusual sites), are often the initial events leading to the diagnosis. After diagnosis, the yearly incidence of thrombotic events is highly variable, and ranges from approximately 1% to 10%. The identification of patients at risk who may benefit from antithrombotic therapy remains a challenge, and it is currently based on age and history of thrombotic events. However, the predictive value of these clinical characteristics is rather limited. Few prospective studies and even fewer interventional randomized studies are available, and there are no studies designed to formally validate the use of risk stratification. The implementation of laboratory parameters such as leukocytosis and/or the JAK2 V617F mutation into a scoring system may be of interest. The mechanisms at work leading to thrombosis remain largely speculative, but are likely to be complex and multifactorial, with a prominent role of cell–cell interactions, mostly owing to qualitative changes. The long‐term treatment options to prevent thrombosis are, schematically, aspirin alone as primary prevention for the low‐risk patients, and cytoreduction combined with aspirin for the other patients. In very low‐risk young essential thrombocythemia patients, abstention can even be considered. The optimal duration of anticoagulation after a thrombotic event is not established. All antithrombotic therapies should be balanced with the hemorrhagic risk, which can also be increased in these patients.